PENINGKATAN KESEHATAN MASYARAKAT MELALUI KEGIATAN SENAM PAGI DI DUSUN KARANG KEMIRI DESA LINGGASARI - royani, sri (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2024)
Karang Kemiri Hamlet is one of the hamlets in Linggasari Village. In order to improve the health level of the residents of this hamlet, healthy exercise is carried out in the morning. Gymnastics is a type of physical sport that involves body exercises that are selected and arranged systematically with the aim of increasing physical fitness, improving skills, and instilling mental and spiritual values. When doing gymnastics, it is usually always accompanied by music. The method used is to arrange an event, time and place that will be participated in by the hamlet residents in this village. The impacts that will be obtained from this morning exercise include increasing the body's immunity and helping to normalize blood flow and train stiff nerves when you wake up. This activity went well and smoothly. This is indicated by the enthusiasm of residents in participating in this activity.